Characterization of the tidal resource in Rathlin Sound. (December 2017) - Pérez-Ortiz, Alberto; Borthwick, Alistair G.L.; McNaughton, James; Avdis, Alexandros
Abstract: Tidal resource assessment is presented for Rathlin Sound, located between Rathlin Island and the north-east coast of Northern Ireland. The flow is simulated in 2D, using the shallow water equations. For an M2 tide, the natural flow conditions exhibit local spatial mean and maximum flow speeds of 2 and 3 m/s. Upper limits to power extraction are about 298 MW for M2 and 330 MW for M2 +S2 tidal signals (different to undisturbed kinetic power and power naturally dissipated at the seabed). An analytical model of a channel connecting two infinite ocean basins underpredicts maximum power extracted in Rathlin Sound due to changes in head driving the flow and the existence of an alternative flow path. At maximum power extracted, there is substantial reduction in mean flow speeds in the strait and to the south-east of Rathlin Sound. In the strait, maximum power is reduced by 14% and 36% for blockage ratios of 80% and 60%. Power extraction both offshore of the island and in the strait yields higher power generation rates than isolated extraction. Resource assessments for Rathlin Sound are generally in good agreement with those for an idealised strait between an island and landmass. Highlights: Tidal resource characterization of Rathlin Sound, a coastal site defined as an island near a landmass. Undisturbed kinetic or dissipated power do not approximate maximum power extracted. Numerical results exceed those from an analytical channel model. Reduction in strait blockage by tidal farm reduces the maximum power extracted. Outcomes of Rathlin Sound agree with those of an idealised island near a landmass.